Kekerasan Objektif dalam Narasi Global War on Terror (GWOT) Analisis GWOT dengan Teori Kekerasan Slavoj Zizek - Kurniawan Dwi Saputra (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2018)
Global War on Terror (GWOT) is a movement to combat terrorism internationally. It involves comprehensive strategy to defeat terrorism in every aspect, from military to economics, from politics to culture. However, the universal imposition of GWOT package includes certain degree of violence. The hidden violences behind GWOT are to be analysed in this research by the light of Slavoj Zizek’s framework regarding types of violence. Zizek classifies violences into two main branchs: subjective and objective. Objective violence consists of two related violences: symbolic, which is a universal imposition of linguistic terms, and systemic, which is smooth functioning of any system.GWOT therefore includes objective violences. First, its universal imposition of binary opposition term in counter-terrorism propaganda, “with us or against us,” represents the very logic of objective violence. Second, GWOT propaganda brings about the production of certain laws that violates the principle of human rights. This systematic abuse is a matter of concern because the factual evidences show us that it does not solve terrorism but rather inspires its reemergence in the future.